Strategi Pengembangan Hotel Berkonsep Syariah di Kota Padang: Studi pada Hotel Rangkayo Basa - Rachmani, Muhammad Ilham; Lioe, Lyly Soemarni (Journal of Information Systems and Management (JISMA), 2024)
Purpose: This research aims to find out the potential for the existence of sharia hotels in supporting halal tourism and the strategy to implement the sharia concept hotel Research Methods: Qualitative and descriptive approach method with SWOT analysis instruments. Data collection techniques include interviews, questionnaires, and documentation. Implication: The results of the data collected are described descriptively, internal and external factors are calculated using a SWOT diagram to obtain the suitable strategy, where the strength factor have higher score compare to weakness factor and the opportunity factor also have higher score toward challenges.